AHOLI BANDLIGI SHAKLLANISHIDA OILAVIY TADBIRKORLIKNING ROLI VA AHAMIYATI - Pardayev, N.S.; Xursanov, S.M. (SCIENCE and SOCIETY, 2024)
This article talks about family entrepreneurship and its role in the country’s development. In particular, the funds created in our country for the establishment of family entrepreneurship, fur ther more and suggestions and recommendations were given for the further development of this field.